2019
DOI: 10.1002/ange.201908694
|View full text |Cite
|
Sign up to set email alerts
|

Au130−xAgx Nanoclusters with Non‐Metallicity: A Drum of Silver‐Rich Sites Enclosed in a Marks‐Decahedral Cage of Gold‐Rich Sites

Abstract: The synthesis and structure of atomically precise Au130−xAgx (average x=98) alloy nanoclusters protected by 55 ligands of 4‐tert‐butylbenzenethiolate are reported. This large alloy structure has a decahedral M54 (M=Au/Ag) core. The Au atoms are localized in the truncated Marks decahedron. In the core, a drum of Ag‐rich sites is found, which is enclosed by a Marks decahedral cage of Au‐rich sites. The surface is exclusively Ag−SR; X‐ray absorption fine structure analysis supports the absence of Au−S bonds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…In terms of large-sized alloy NCs, Jin and co-workers synthesized Au 130Àx Ag x (TBBT) 55 (x =~98) in 2019. [168] Monometallic Au 130 (TBBT) 55 has not been reported. Therefore, Au 130Àx Ag x (TBBT) 55 (x =~98) is considered at ype of alloy NC formed for the first time by alloying Au and Ag.…”
Section: [Au 25àmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of large-sized alloy NCs, Jin and co-workers synthesized Au 130Àx Ag x (TBBT) 55 (x =~98) in 2019. [168] Monometallic Au 130 (TBBT) 55 has not been reported. Therefore, Au 130Àx Ag x (TBBT) 55 (x =~98) is considered at ype of alloy NC formed for the first time by alloying Au and Ag.…”
Section: [Au 25àmentioning
confidence: 99%
“…Regarding the electronic structureo fA u 130Àx Ag x (TBBT) 55 ,o ptical absorption spectroscopy ( Figure 26 A) and ultrafastl aser spectroscopy (Figures 26 B-D) have revealed that it does not display metallicproperties. [168] 3. 84 were used as precursors because all of these Au n (SR) m NCs can be selectively synthesized or isolated.…”
Section: [Au 25àmentioning
confidence: 99%
“…To understand the coordination of Ag atoms in the AuAg catalysts, which is an important factor for determining the surface energy and consequential catalytic activity, we performed EXAFS analysis (Figure S15). The initial AuAg-R and AuAg-B catalysts showed under-coordinated Ag atoms with different coordination numbers owing to the NP size and alloyed structure. AuAg-R had a smaller coordination number than AuAg-B (Table S2), originating from the different particle sizes and alloy arrangements. TEM/SEM images and ECSA measurements showed that AuAg-R had a smaller particle size and higher surface area than AuAg-B (Figure and Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Doping and alloying are employed for two important purposes. Because the costs of noble metals are similar, the combination of noble metals to each other is used for amplification purposes or to change the emitted light properties. ,, The combination of Au and Ag atoms is the most popular application of metal alloy NCs in biosensors. , There are reports that represented the amplification effect of Ag atoms on the PL of AuNCs. , Various PL biosensing strategies have been developed using bimetallic Ag/Au NCs including turn-off, assembly induced emission, photoinduced election transferring, , and FRET- based strategies. This is due to their significant synergistic effect that boosts the analytical signals and the performance of the sensing surface .…”
Section: Metal Ncsmentioning
confidence: 99%
“…Because the costs of noble metals are similar, the combination of noble metals to each other is used for amplification purposes or to change the emitted light properties. 432,521,522 The combination of Au and Ag atoms is the most popular application of metal alloy NCs in biosensors. 523,524 There are reports that represented the amplification effect of Ag atoms on the PL of AuNCs.…”
Section: Dopping and Alloying Of Ncs For Diagnosticsmentioning
confidence: 99%